Instagram multiple accounts: a self-presentation by Generation Z - Putranto, Teguh Dwi; Murwani, Endah; Prasetyo, Dwi (Faculty of Communications Science, Dr. Soetomo University, 2025)
New media exists to meet human needs, especially the need for information and self-expression. However, users need to adapt to utilise it, and this adaptation process varies from person to person, including Generation Z. Generation Z is one of the generations that quickly adapts to the presence of new media compared to previous generations. The ease with which Generation Z uses new media such as Instagram also makes Generation Z use the new media. Some members of Generation Z even have several social media accounts at the same time. Based on this background, the purpose of this study is to find out how self-presentation by Generation Z occurs when using multiple Instagram accounts. This research used a descriptive qualitative approach as the research method. The data collection technique employed is Focus Group Discussion (FGD), where the participants are members of Generation Z. There were 10 high school students as participants. The sampling method used in this study was snowball sampling. The conclusion of this research shows that the use of Instagram multiple accounts by Generation Z is indicative of a sophisticated self-presentation technique. The main account provides a formal setting for creating an idealised persona and obtaining approval from others. With a smaller audience, secondary accounts provide a forum for more genuine, impromptu, and emotional self-expression. Other accounts, meanwhile, provide chances to experiment with different characters, interests, and identities. These self-presentations show how Generation Z balances the personal identity they want to preserve in the digital sphere with the social image they want to convey.